STRATEGI PENGEMBANGAN KOPERASI PETERNAK GALUR MURNI DI KABUPATEN JEMBER - Dany Alifah Irawati; Musa Hubeis; Muksin Muksin (School of Business, Bogor Agricultural University (SB-IPB), 2017)
The objective of the research is to identify the internal and external environment condition in (Galur Murni Cattle breeder cooperation), Koperasi Peternak Galur Murni to analyze the strategic alternative to be implemented in the development of Koperasi Peternak Galur Murni and to prioritize development strategy of Koperasi Peternak Galur Murni in the future. The analysis covered descriptive analysis, Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), Internal-External (IE) matrix analysis, Strengths, Weaknesses, Opportunities and Threat (SWOT) and Analytical Hierarchy Process (AHP). The result shows that the strategic factor that becomes the main strength with relatively high importance is Quality Control system for milk received from the farmers. The alternative strategy that can be implemented in KPGM is increasing the promotion activities by socializing the importance of drinking milk, production activities efficiency by arranging a Standard Operational Procedure (SOP), strengthening of cooperation, registering the product to Food and Drug Control Agency/Badan Pengawas Obat dan Makanan (BPOM), conducting intensive communication with all the cooperation members, using the appropriate technology in production activities, diversification of products, strengthening the modal through loan and coordinating with the government to get assistance in strengthening the cooperation and breeder. The AHP results shows that the strategic priority is 1) the strengthening of the modal through financial institution, 2) increasing the promotion activities by socializing the importance of drinking milk, 3) product diversification and 4) conducting coordination with the local government and animal husbandry department and UMKM department Keywords: cooperation breeder pure lines, development strategy, IFE, EFE, SWOT AbstrakPenelitian ini bertujuan mengidentifikasi kondisi lingkungan internal dan eksternal Koperasi Peternak Galur Murni, menganalisis alternatif strategi yang dapat diterapkan dalam pengembangan Koperasi Peternak Galur Murni, dan menentukan prioritas strategi pengembangan Koperasi Peternak Galur Murni di masa datang. Metode analisis data yang digunakan meliputi analisis deskriptif, analisis Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), analisis matrik Internal-External (IE), Strengths, Weaknesses, Opportunities dan Threats (SWOT) dan Analytical Hierarchy Process (AHP). Hasil penelitian menunjukkan faktor strategik yang menjadi kekuatan utama dengan kepentingan relatif tertinggi adalah sistem Quality Control (QC) untuk peneriman susu dari peternak. Alternatif strategi yang dapat diterapkan di KPGM adalah peningkatan kegiatan promosi dengan sosialisasi pentingnya minum susu, efisiensi kegiatan produksi dengan penyusunan Standard Operational Procedure (SOP), penguatan kelembagaan koperasi, melakukan pendaftaran produk ke Badan Pengawas Obat dan Makanan (BPOM), melakukan komunikasi intensif dengan semua anggota koperasi, pemanfaatan teknologi tepat guna dalam kegiatan produksi, diversifikasi produk, penguatan permodalan melalui pinjaman selain lembaga keuangan dan melakukan koordinasi dengan pemerintah daerah untuk bantuan penguatan koperasi dan peternak. Hasil analisis AHP, strategi prioritasnya adalah 1) penguatan modal melalui lembaga keuangan, 2) peningkatan kegiatan promosi dengan sosialisasi pentingnya minum susu, 3) diversifikasi produk, dan 4) melakukan koordinasi dengan Pemerintah Daerah serta Dinas Peternakan dan Dinas UMKM.Kata kunci: koperasi peternak galur murni, strategi pengembangan, IFE, IFE, SWOT